How language can be used to promote gender equality in geoscience - Nardini, Olga; Bandecchi, Anna Elisa; Tofani, Veronica; Intrieri, Emanuele (Frontiers in Earth Science, 2023)
Gender inequality is detrimental to individuals and ultimately to organizations. Furthermore, addressing this issue will become more important to be eligible for research funds, as already occurs in Europe. Since language shapes the way we think, some simple changes in the words we use daily in geoscience and in other academic fields could promote gender equality. Journal editorial boards could adopt similar measures to foster such changes in the geoscience community.